Marriage policies and indigenous practices: Doctrine of Belén, Altos de Arica (1763-1823) - Inostroza Ponce, Xochitl (2013)
Using records of marriages and marriage informations for the Doctrine of Belén, the main ecclesiastical laws that established norms for the formation of new families in the Indian villages of the highlands of Arica in late eighteenth and early nineteenth century were analyzed. Rather than attempting to adjust reality to the standard, the information contained in both types of sources coincide with the interpretations that suggest a degree of adaptation to indigenous practices, which may have caused the successful incorporation of Christian marriage to the community ritual system for the Doctrine of Bethlehem in the late colonial period.